Therapeutic Potentials of Microalgae in the Treatment of Alzheimer’s Disease - Tosin A. Olasehinde; Ademola O. Olaniran; Anthony I. Okoh (Molecules, 2017)
Current research is geared towards the discovery of new compounds with strong neuroprotective potential and few or no side effects compared to synthetic drugs. This review focuses on the potentials of extracts and biologically active compounds derived from microalgal biomass for the treatment and management of Alzheimer’s disease (AD). Microalgal research has gained much attention recently due to its contribution to the production of renewable fuels and the ability of alga cells to produce several secondary metabolites such as carotenoids, polyphenols, sterols, polyunsaturated fatty acids and polysaccharides. These compounds exhibit several pharmacological activities and possess neuroprotective potential. The pathogenesis of Alzheimer’s disease (AD) involves complex mechanisms that are associated with oxidative stress, cholinergic dysfunction, neuronal damage, protein misfolding and aggregation. The antioxidant, anticholinesterase activities as well as the inhibitory effects of some bioactive compounds from microalgae extracts on β-amyloid aggregation and neuronal death are discussed extensively. Phytochemical compounds from microalgae are used as pharmaceuticals, nutraceuticals and food supplements, and may possess neuroprotective potentials that are relevant to the management and/or treatment of AD.